1998
DOI: 10.1073/pnas.95.3.1336
|View full text |Cite
|
Sign up to set email alerts
|

Grandmothering, menopause, and the evolution of human life histories

Abstract: Long postmenopausal lifespans distinguish humans from all other primates. This pattern may have evolved with mother-child food sharing, a practice that allowed aging females to enhance their daughters' fertility, thereby increasing selection against senescence. Combined with Charnov's dimensionless assembly rules for mammalian life histories, this hypothesis also accounts for our late maturity, small size at weaning, and high fertility. It has implications for past human habitat choice and social organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
880
11
10

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,104 publications
(942 citation statements)
references
References 49 publications
41
880
11
10
Order By: Relevance
“…A review of the ethnographic literature with a particular focus on South Africa has shown that women also provide a great deal of meat resources through less-prestigious activities such as snaring, trapping, and collecting of shellfish (Wadley, 1998). For at least some huntergatherer groups, provisioning from older, post-reproductive females is one of the most important sources of nutrition for a family unit (Hawkes et al, 1998;Hill and Hurtado, 2009) . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65…”
Section: Hunters and Gatherers In The Archaeological Record At Bbcmentioning
confidence: 99%
“…A review of the ethnographic literature with a particular focus on South Africa has shown that women also provide a great deal of meat resources through less-prestigious activities such as snaring, trapping, and collecting of shellfish (Wadley, 1998). For at least some huntergatherer groups, provisioning from older, post-reproductive females is one of the most important sources of nutrition for a family unit (Hawkes et al, 1998;Hill and Hurtado, 2009) . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65…”
Section: Hunters and Gatherers In The Archaeological Record At Bbcmentioning
confidence: 99%
“…While gathering evidently played an important role over the whole of human evolution, hunting, although introduced later, coincided with 'a major leap for mankind' and has ever since played the most dominating cultural role. While hunting may have overtaken gathering in cultural importance, gathering continued to play a very important nutritional role, because: (i) gathering still contributes about 65 % to the subsistence base; (ii) many micronutrients derive only from plant sources; (iii) gathering of, for example, shellfish provides a substantial amount of LCP and other nutrients essential for brain development; and (iv) gathering plays an important cultural role since women, children and grandparents can participate (56,57,317) .…”
Section: Anthropologymentioning
confidence: 99%
“…Humans are also unusual amongst mammals in that males are often involved in provisioning females and offspring, though the degree of male help varies considerably across cultures (Hill, 1982). Both male involvement in raising children and help from female kin may underlie the evolution of a number of human life history patterns (Hill, 1993;Hawkes et al, 1997Hawkes et al, , 1998Kaplan et al, 2000). For example, help from kin may be responsible for the relatively short interbirth intervals of human females, compared to the other great apes (Hawkes et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Both male involvement in raising children and help from female kin may underlie the evolution of a number of human life history patterns (Hill, 1993;Hawkes et al, 1997Hawkes et al, , 1998Kaplan et al, 2000). For example, help from kin may be responsible for the relatively short interbirth intervals of human females, compared to the other great apes (Hawkes et al, 1998). The females of other ape species must ensure that their offspring are relatively self-sufficient by the time they are weaned.…”
Section: Introductionmentioning
confidence: 99%